T47. Is stuttering a focal dystonia?. (May 2018) - Vreeswijk, Sarah M.; Linh Hoang, T.N.; Neef, Nicole E.; Gudenberg, Alexander; Paulus, Walter; Sommer, Martin
Abstract : Introduction: Persistent developmental stuttering (PDS) disrupts speech fluency in about 1% of adults, predominantly males. Its etiology remains unclear. PDS shares clinical characteristics with focal, task specific dystonias. Both disorders are associated with excessive activity in muscles not needed to perform a desired movement. Both disorders are task specific and spare other functions of the involved muscle groups. Both disorders have been linked to disturbed movement preparation in the primary motor cortex (Gilio et al., 2003; Neef et al., 2015 ). Previously, we probed the balance of inhibition and facilitation in the primary motor cortex. We observed that in PDS, the major impairment of this motor cortical, interneuronal balance is a reduced intracortical facilitation during rest (Neef et al., 2011 ). This is in contrast to focal dystonia, where intracortical inhibition during rest is deficient (Ridding et al., 1995 ). In dystonia, the impairment of inhibition extends into the sensory domain and leads to a sensory overflow which cannot be properly handled by the brain. This has been shown using median and ulnar nerve somatosensory evoked potentials either stimulated separately or simultaneously. In patients, simultaneous stimulation yielded greater central amplitudes than the arithmetic sum of amplitudes of the separately obtained single nerve stimulations. In healthy controls, the amplitudes from bi-nerval stimulation were smaller than the sum of the amplitudes after single nerve stimulation (Tinazzi et al., 2000 ). Methods: We studied somatosensory evoked potentials in adults who stutter, testing the processing of dual sensory input. In 15 adults who stutter (aged 15–55 years; 3 females) and 14 matched fluent speaking adults, we recorded somatosensory evoked potentials (SEPs) at C5' and C6' induced by stimulating separately or simultaneously the tongue and the cheek at the corner of the mouth. We calculated amplitude ratios by dividing amplitudes from simultaneous stimulation by the sum of those from separate stimulation. Results: Amplitude ratios did not differ between groups, indicating normal processing of dual sensory input (Vreeswijk et al., 2011 ). Conclusion: The pathophysiology of the two disorders differs. Focal dystonias are characterized by an impaired inhibition of surrounding muscles (Mink, 1996 ). It is conceivable that in stuttering, the inhibition is normal, but the center is not adequately facilitated, resulting in a compensatory facilitation of the surrounding muscles, thereby leading to the hyperactivity of the articulators observed clinically. This inverted center surround hypothesis will be tested experimentally.